Innovative Insulation Materials: A Comprehensive Review of Current Trends, Challenges, and Future Directions in Sustainable Building Technologies - Erzen, Buket; Karatas, Mukaddes; Orhan, Ramazan; Aydogmus, Ercan (Taylor & Francis Inc, 2025)
This research redefines the future potential of insulation materials, considering not only energy efficiency but also environmental, health, and economic impacts in sustainable construction applications. It goes beyond traditional insulation materials and discusses smart, biological, and liquid insulation solutions and digitalized production processes. The evolution of insulation materials serves the goals of creating healthy living spaces in buildings and minimizing environmental impacts. Insulation materials have evolved significantly, transforming from basic thermal and sound insulation tools into multifaceted solutions that address energy efficiency, environmental sustainability, and indoor health. This comprehensive review explores the historical development, classification, and innovative advancements in insulation technologies, with a particular focus on thermal, sound, and advanced materials. Emerging solutions, such as biobased and nanotechnology-enabled materials, offer lower environmental footprints and superior performance compared to traditional options. These advancements play a pivotal role in reducing greenhouse gas emissions, optimizing energy consumption, and supporting global sustainability goals. The integration of smart and adaptive insulation technologies further underscores the potential of these materials in reshaping sustainable construction practices. By analyzing the economic, environmental, and functional impacts of various insulation materials, this study highlights their critical role in addressing climate change, improving living environments, and advancing building technologies.
Keywords: Biobased materials; energy efficiency; nanotechnology in construction; smart building technologies; sustainable insulation